The Effectiveness of Inquiry Learning Model with Concept Mapping Technique on Metacognitive Awareness on Senior High School Students in Class X - Putri Novitasari; Suratno Suratno; Mochammad Iqbal (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2021)
This study aims to determine the effect of metacognitive awareness of high school students in using the inquiry learning model with Concept mapping techniques. This study used a quasi-experimental study involving students of class X Mathematics and Natural Sciences as the experimental group and the control group. The experimental group applied the inquiry learning model with Concept mapping techniques, while the control group applied the STAD learning model with information discussions by forming a small group. Kolmogorov Smirnov's one sample test and homogeneity were used to select the experimental group and the control group. The measurement of students' metacognitive awareness in this study used an MAI (Metacognitive Awareness Inventory) questionnaire. The number of questions consists of 35 items, where the question is divided into three factors involved in the knowledge of consciousness, and five other factors related to the regulation of consciousness. The data on the value of metacognitive awareness used to measure students' metacognitive awareness was obtained from the MAI questionnaire given to students both in the experimental class and in the control class before and after the study, the data obtained was then analyzed using the ANAKOVA test. MAI treatment has a probability value of 0.008 which is smaller than 0.05 (p = 0.008 <0.05) which means that there is a significant influence on the inquiry learning model with Concept mapping techniques on students' metacognition. Based on the Normalized gain test, the n-gain value is 0.